Alliance and technology networks: an empirical study on technology learning. (14th February 2007) - Kim, Changsu; Beldona, Sam; Contractor, Farok J.
Patterns of alliance ties and patent citations, between firms in the chemical-pharmaceutical sector over a 13-year period, were mapped to draw alliance and technology networks in the industry. We then investigated how technology learning takes place in the networks. Learning was particularly high when the allies have had direct interorganisational ties, and when both allies have accessed the common pool of external or third-party knowledge. The results emphasise the importance of developing trust around direct alliance ties. There appears to be a tension however, concerning the extent to which firms should have similar or different technology profiles, in order to learn most effectively from each other. The results suggest that learning is most likely when partners are similar in their technology base at the network level, but still remain distinctive in their dyadic technology profiles.